1999
DOI: 10.1080/004982599238335
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of artelinic acid to dihydroqinghaosu by human liver cytochrome P4503A

Abstract: 1. Artelinic acid (AL), a water-soluble artemisinin analogue for treatment of multidrug resistant malaria, is metabolized to the active metabolite dihydroqinghaosu (DQHS) solely by CYP3A4/5. Although AL is not metabolized by CYP2C9, it does inhibit diclofenac 4-hydroxylase activity with an IC50 = 115 microM. Interestingly, AL activates CYP2D6-mediated bufuralol metabolism in human liver microsomes but not recombinant CYP2D6-Val by approximately 30% at AL concentrations up to 100 microM. 2. In human liver micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…The most reasonable choice seems to be the use of dihydroartemisinin for in vitro assays since this derivative is relatively stable and all currently used artemisinin derivatives and those that are under advanced phases of development are rapidly transformed into dihydroartemisinin in humans. [14][15][16][17] The significant positive correlation between the in vitro responses to chloroquine and monodesethylamodiaquine or quinine and between the response to mefloquine and halofantrine is in agreement with in vivo resistance to amodiaquine, quinine, and halofantrine observed in Southeast Asia where a high level of resistance to chloroquine and mefloquine has emerged. 41,42 Cross-resistance between pyrimethamine and cycloguanil has also been observed in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The most reasonable choice seems to be the use of dihydroartemisinin for in vitro assays since this derivative is relatively stable and all currently used artemisinin derivatives and those that are under advanced phases of development are rapidly transformed into dihydroartemisinin in humans. [14][15][16][17] The significant positive correlation between the in vitro responses to chloroquine and monodesethylamodiaquine or quinine and between the response to mefloquine and halofantrine is in agreement with in vivo resistance to amodiaquine, quinine, and halofantrine observed in Southeast Asia where a high level of resistance to chloroquine and mefloquine has emerged. 41,42 Cross-resistance between pyrimethamine and cycloguanil has also been observed in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…[10][11][12][13] Although pharmacokinetic data are incomplete, it has been established that all currently available artemisinin derivatives are metabolized rapidly to dihydroartemisinin, the biologically active main human metabolite. [14][15][16][17] In the case of sodium artesunate, the aqueous solution that is reconstituted by dissolving the anhydrous powder of the drug in 5% dextrose solution just before parenteral administration is known to hydrolyze the compound rapidly into dihydroartemisinin. 18 Initial in vitro studies on laboratory-adapted clones of P. falciparum have shown that dihydroartemisinin is more active than the other artemisinin derivatives.…”
mentioning
confidence: 99%
“…Sixty-four (64) different individuals representing persistent or new infections were genotyped for the cytochrome P450 3A4 392A>G and 2B6 516G>T and for the UDP-glucuronosyltransferase UGT2B7 802C>T, which are all involved in the metabolism of artemisinin drugs and/or lumefantrine. [15][16][17][18] Sequencing of cytochrome P450 3A4 was successfully performed for 56/64 participants. Results from sequencing of cytochrome P450 3A4 showed homozygote wild-type carriers at position 392, i.e., adenosine, for all 56 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Artemisinin derivatives are mainly metabolized by the human cytochrome P450 3A4 16 and 2B6 18 and also by the metabolic enzyme UDP-glucuronosyltransferase UGT2B7 . 17 The lumefantrine component of Coartem is also metabolized by CYP3A4 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, it is a gametocidal agent found to be highly effective against malaria caused by multidrug-resistant Plasmodium falciparum (Tran et al, 1996;Van Hensbroek et al, 1996;Makanga, 2014). Being a BCS class II drug, it exhibits poor solubility and high lipophilicity (log p of 3.8), and undergoes extensive hepatic first-pass effect and metabolism by CYP3A4 isozymes, leading eventually to its low oral bioavailability (i.e.,545%) (Van Hensbroek et al, 1996;Grace et al, 1999). Multiple drug delivery systems like, micronization, solid dispersions (Shah & Mashru, 2008), inclusion complexes (Yang et al, 2009), complexation with hydrophilic polymers (Jain & Gupta, 2008) and supersaturable systems (Mandawgade et al, 2008) have been explored for enhancing the oral bioavailability of artemether, yet none of these formulations are considered to be highly satisfactory for enhancing the oral bioavailability ostensibly owing to their dissolution rate enhancement characteristics only.…”
Section: Introductionmentioning
confidence: 99%